Optimal Environmental Policy Differentials under Emissions Constraints - Raymond J.G.M. Florax; Abay Mulatu; Cees A. Withagen (Tinbergen Institute, 2003)
Is there a case to be made for preferential treatment of the exposed sector in an economy when compliance to an aggregate emissions constraint induced by an international environmental agreement is mandatory? This question is being debated in many countries, including The Netherlands, in the context of the implementation of the Kyoto protocol. We address this issue in a general equilibrium framework in this paper, and theoretically cover several market structures, including perfect competition, oligopoly and the large country case. Our main finding is that in many circumstances preferential treatment is not warranted from the point of view of maximizing social welfare.
Keywords: D6; F12; Q28; 330; ecological dumping; general equilibrium; emissions constraints; Kyoto protocol; Umweltstandard; Umweltpolitik; Internationale Wirtschaft; Soziale Wohlfahrtsfunktion